2021
DOI: 10.3389/fpsyg.2021.759454
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Prevalence of Diabetes Distress and Determining Its Psychosocial Predictors Among Saudi Adults With Type 2 Diabetes: A Cross-Sectional Study

Abstract: In recent years, the global burden of diabetes distress has increased significantly worldwide, imposing mental health issues on patients and the healthcare system. Hence, this study aimed to estimate the prevalence of diabetes distress and determine its psychosocial predictors among Saudi adults with type 2 diabetes mellitus (T2DM). This cross-sectional, observational study was conducted at Diabetes Clinics, Tertiary Care Academic Medical Center, King Saud University Medical City, Riyadh, Saudi Arabia. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…In the current study, diabetes duration, complications and treatment regimen were all associated with increased risks for comorbid DD, depression, and anxiety symptoms, which is consistent with previous studies (53,55,58). However, it is difficult to interpret potential risk factors for mental health disorders in T2DM as these factors often coexist and interact with each other.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the current study, diabetes duration, complications and treatment regimen were all associated with increased risks for comorbid DD, depression, and anxiety symptoms, which is consistent with previous studies (53,55,58). However, it is difficult to interpret potential risk factors for mental health disorders in T2DM as these factors often coexist and interact with each other.…”
Section: Discussionsupporting
confidence: 85%
“…The current study's bivariant analysis showed that illiteracy, insufficient family income, unemployment, and being divorced or widowed were associated with higher prevalence of DD, depression, and anxiety symptoms. Study findings from other countries also showed similar association although not all associations were statistically significant (53,58). Consequently, optimizing management of patients with DM does not only require a multidisciplinary team of healthcare workers, but it also involves synergistic multi-dimensional care plan of the surrounding environment.…”
Section: Discussionmentioning
confidence: 59%
“…The prevalence of distress was high among patients with diabetes (Batais et al, 2021). Simultaneous increases in blood glucose levels due to diabetes distress have also been reported (Dekkers & Hertroijs, 2018;Pranata et al, 2022).…”
Section: Introductionmentioning
confidence: 77%
“…Depression and anxiety among patients with T2DM also are associated with female gender and the existing of these psychological problems also is associated with increased symptoms of diabetes distress [39,48,49]. Increased attention and support for diabetes distress are recommended for females with T2DM [50].…”
Section: Discussionmentioning
confidence: 99%